Retention, persistence, and writing programs - Ruecker, Todd, editor; Shepherd, Dawn, editor; Estrem, Heidi, editor; Brunk-Chavez, Beth, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2017)
Perspectives on how first-year writing can support or hinder students' transitions to college from scholars working in a variety of institutional and geographic contexts and a range of student populations. Contributors present individual and program case studies, surveys of thousands of students, retention data, and policy analysis.--Provided by publisher.
Introduction: retention, persistence, and writing: expanding the conversation / Todd Ruecker, Dawn Shepherd, Heidi Estrem, and Beth-Brunk Chavez -- Retention Panopticon: what WPAS should bring to the table in discussions of student success / Rita Malenczyk -- Building collaborative partnerships to support institutional-level retention initiatives in writing programs / Ashley J. Holmes and Cristine Busser -- Big data and writing program retention assessment: what we need to know / Marc Scott -- The imperative of pedagogical and professional development to support the retention of underprepared students at open-access institutions / Joanne Giordano, Holly Hassel, Jennifer Heinert, and Cassandra Phillips -- How student performance in first-year composition predicts retention and overall student success / Nathan Garrett, Matthew Bridgewater, and Bruce Feinstein -- "Life gets in the way": the case of a seventh-year senior / Sara Webb-Sunderhaus -- Absolute hospitality in the writing program / Pegeen Reichert Powell -- Retention, critical pedagogy, and students as agents: eschewing the deficit model / Beth Buyserie, Anna Plemons, and Patricia Freitag Ericsson -- Reconfiguring the writing studio model: examining the impact of the PlusOne Program on student performance and retention / Polina Chemishanova and Robin Snead -- Retention rates of second language writers and basic writers: a comparison within the Stretch Program model / Sarah Elizabeth Snyder -- The kairotic classroom: retention discourse and supplemental instruction in the first year / Sarah E. Harris -- Enhancing alliances and joining initiatives to help students: the story of how we created developmental learning communities at Texas A&M University-Corpus Christi / Susan Wolff Murphy and Mark Hartlaub -- Undergraduate mentors as agents of engagement: peer advocates in first-year writing courses / Michael Day, Tawanda Gipson, and Chris Parker -- Afterword / Linda Adler-Kassner.
Keywords: English language -- Rhetoric -- Study and teaching (Higher); College dropouts -- Prevention